1997
DOI: 10.1073/pnas.94.19.10098
|View full text |Cite
|
Sign up to set email alerts
|

The small GTP-binding protein Rho links G protein-coupled receptors and Gα 12 to the serum response element and to cellular transformation

Abstract: Receptors coupled to heterotrimeric G proteins can effectively stimulate growth promoting pathways in a large variety of cell types, and if persistently activated, these receptors can also behave as dominant-acting oncoproteins. Consistently, activating mutations for G proteins of the G␣ s and G␣ i2 families were found in human tumors; and members of the G␣ q and G␣ 12 families are fully transforming when expressed in murine fibroblasts. In an effort aimed to elucidate the molecular events involved in prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
231
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(252 citation statements)
references
References 41 publications
20
231
1
Order By: Relevance
“…Right panel: C3 transferase functions in Ishikawa cells to inhibit activation of the serum response element (SRE) reporter by RhoA, but not by Cdc42Hs. Transfections were performed with constituitively activating mutants, RhoQL (400 ng) and Cdc42QL (400 ng) (Coso et al, 1995) and SRE-luciferase reporter (1 mg) in the presence (+) or 100 ng pCEV-C3 transferase (C3) (Fromm et al, 1997). pCEV-0 at 100 ng was used as a control (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Right panel: C3 transferase functions in Ishikawa cells to inhibit activation of the serum response element (SRE) reporter by RhoA, but not by Cdc42Hs. Transfections were performed with constituitively activating mutants, RhoQL (400 ng) and Cdc42QL (400 ng) (Coso et al, 1995) and SRE-luciferase reporter (1 mg) in the presence (+) or 100 ng pCEV-C3 transferase (C3) (Fromm et al, 1997). pCEV-0 at 100 ng was used as a control (7).…”
Section: Discussionmentioning
confidence: 99%
“…Control expression vector (pCEV-0) was added to give a total of 500 ng of plasmid per well. pCEV-C3 transferase expression plasmid was prepared as described in Fromm et al, 1997. Ishikawa cells were stably transfected with either a FLAG epitope-tagged Brx expression plasmid, or control plasmid encoding Neomycin resistance (pBK-RSV).…”
Section: Cell Culture and Transient Transfectionmentioning
confidence: 99%
“…Furthermore, the expression of the Ga 12 QL has been shown to stimulate DNA synthesis in several other cell-types such as 1321N1 astrocytoma cells (Aragay et al, 1995). Studies from several laboratories including ours have shown that the proliferative pathway regulated by Ga 12 includes the Ras/Rac mediated activation of JNKs (Vara Prasad et al, 1995;Collins et al, 1996;Voyno-Yasenetskaya et al, 1996), Rho-dependent activation of cytoskeletal changes (Buhl et al, 1995;Hooley et al, 1996;Needham and Rozengurt, 1998), Rho-dependent activation of speci®c transcription factors (Fromm et al, 1997), Rac/MEKK1-mediated activation of AP-1 complex (Collins et al, 1996), and Ras/Rac/Rhodependent cell transformation (Zhang et al, 1996;Tolkacheva et al, 1997;Fromm et al, 1997). In addition, it has been shown that serum-induced phospholipase A 2 (PLA 2 ) activity was potentiated by Ga 12 QL in NIH3T3 cells, suggesting a role for eicosanoids in Ga 12 QL signaling (Xu et al, 1993).…”
mentioning
confidence: 87%
“…NIH3T3 cells transformed with Ga 12 QL or Ga 13 QL indicated that conventional secondary messenger pathways involving cAMP, Ca 2+ , or IP 3 were not altered in these cells (Chan et al, 1993;Xu et al, 1993;Jiang et al, 1993Vara Prasad et al, 1994;VoynaYasenetskaya et al, 1994). However, speci®c sets of primary respose genes appear to be activated in Ga 12 QL-and Ga 13 QL-transformed NIH3T3 cells (Fromm et al, 1997;Vara Prasad et al, 1994). Ga 12 QL has been shown to activate SRFs through a Rho-dependent pathway (Fromm et al, 1997).…”
Section: Ga 12/13 : the Gep Oncogenes?mentioning
confidence: 99%
“…However, speci®c sets of primary respose genes appear to be activated in Ga 12 QL-and Ga 13 QL-transformed NIH3T3 cells (Fromm et al, 1997;Vara Prasad et al, 1994). Ga 12 QL has been shown to activate SRFs through a Rho-dependent pathway (Fromm et al, 1997). Ga 13 QL has been shown to activate the transcription of Egr-1 a primary response gene implicated in cell proliferation as well as di erentiation .…”
Section: Ga 12/13 : the Gep Oncogenes?mentioning
confidence: 99%